ChemInform Abstract: Copper‐Catalyzed Enantioselective Intramolecular Aryl C—N Coupling: Synthesis of Enantioenriched 2‐Oxo‐1, 2, 3, 4‐tetrahydroquinoline‐3‐carboxamides via an Asymmetric Desymmetrization Strategy. Issue 23 (June 2015) - He, Nian; Huo, Yanping; Liu, Jianguang; Huang, Yusha; Zhang, Shasha; Cai, Qian
Abstract The products are obtained in good yields and with moderate enantiomeric excess.